The warm south : how the Mediterranean shaped the British imagination - Holland, R. F. (Robert F.) (Yale scholarship online., 2018)
An evocative exploration of the impact of the Mediterranean on British culture, ranging from the mid-eighteenth century to today Ever since the age of the Grand Tour in the eighteenth century, the Mediterranean has had a significant pull for Britons--including many painters and poets--who sought from it the inspiration, beauty, and fulfillment that evaded them at home. Referred to as "Magick Land" by one traveler, dreams about the Mediterranean, and responses to it, went on to shape the culture of a nation. Written by one of the world's leading historians of the Mediterranean, this book charts how a new sensibility arose from British engagement with the Mediterranean, ancient and modern. Ranging from Byron's poetry to Damien Hirst's installations, Robert Holland shows that while idealized visions and aspirations often met with disillusionment and frustration, the Mediterranean also offered a notably insular society the chance to enrich itself through an imagined world of color, carnival, and sensual self-discovery